2006
DOI: 10.1074/jbc.m601335200
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Produced in Response to Engagement of β2 Integrins on Human Neutrophils Activates the Monomeric GTPases Rap1 and Rap2 and Promotes Adhesion

Abstract: We found that engagement of ␤2 integrins on human neutrophils increased the levels of GTP-bound Rap1 and Rap2. Also, the activation of Rap1 was blocked by PP1, SU6656, LY294002, GF109203X, or BAPTA-AM, which indicates that the downstream signaling events in Rap1 activation involve Src tyrosine kinases, phosphoinositide 3-kinase, protein kinase C, and release of calcium. Surprisingly, the ␤2 integrin-induced activation of Rap2 was not regulated by any of the signaling pathways mentioned above. However, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 68 publications
3
19
1
Order By: Relevance
“…It also appears that the RGD sequence itself is not essential for activation as integrin α9β1 does not use RGD as a binding motif (Yokasaki and Sheppard, 2000). Furthermore, specific β-subunits do not appear to be essential because β2 integrins also induce NO production in neutrophils (Jenei et al, 2006). Instead, our results suggest that the α-subunit, and specifically its cytoplasmic domain, is the key determinant for integrin-induced iNOS activation.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…It also appears that the RGD sequence itself is not essential for activation as integrin α9β1 does not use RGD as a binding motif (Yokasaki and Sheppard, 2000). Furthermore, specific β-subunits do not appear to be essential because β2 integrins also induce NO production in neutrophils (Jenei et al, 2006). Instead, our results suggest that the α-subunit, and specifically its cytoplasmic domain, is the key determinant for integrin-induced iNOS activation.…”
Section: Discussioncontrasting
confidence: 52%
“…As components of the protein signaling pathways that transduce integrin and NO effects are shared, such as Src and Rac-1 noted above, we wished to determine whether there are interactions between integrins and iNOS and whether this interaction might modulate cell migration. Previous studies have reported that, when activated, β2 integrins expressed on neutrophils can stimulate NO production (Jenei et al, 2006). However, whether this effect occurs by means of β1 integrins and the nature by which NO might subsequently modulate integrin-associated cell migration are incompletely understood.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies of Rap2 proteins were limited and often focused on comparison with Rap1 (36,(41)(42)(43)(44), whereas Nore1B/RAPL protein was mainly considered as an effector of Rap1 in lymphocytes (13,14). Although Rap1 and Rap2 proteins are closely related (40), the functional link between Rap2 and RAPL has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of DN-Rap1 (Rap1N17) significantly inhibited neurite outgrowth, whereas WT-and CA-Rap1 (Rap1 V12) did not affect it in response to NGF ( Figure 3B). A putative inhibitor of Rap1, 8CPT-cGMP (Jenei et al, 2006), significantly The interaction of Rap1 and RhoA in response to NGF was examined. Serum-starved PC12 cells were treated with 100 ng/ml NGF for various times as indicated and lysed.…”
Section: Rap1 Is Also Involved In Neurite Outgrowth Of Pc12 Cells Indmentioning
confidence: 99%